Are MXenes suitable as cathode materials for rechargeable Mg batteries?. Issue 6 (14th April 2020) - Kaland, Henning; Hadler-Jacobsen, Jacob; Fagerli, Frode Håskjold; Wagner, Nils P.; Wang, Zhaohui; Selbach, Sverre M.; Vullum-Bruer, Fride; Wiik, Kjell; Schnell, Sondre Kvalvåg
Abstract : The feasibility of MXenes as energy dense cathodes for rechargeable Mg batteries is assessed, revealing major challenges but also some promise. Abstract : MXenes, a type of two-dimensional transition metal carbide/nitride, have received significant attention for electrochemical storage applications. With substantial capacities predicted for Mg ions, MXenes have been considered a promising candidate for cathode materials for rechargeable Mg batteries (RMBs). While there have been reports demonstrating reversible capacities of 100–200 mA h g −1 for MXene-based cathodes, the understanding of the reactions occurring is limited. Here, we investigate unsolvated Mg 2+ intercalation into multi-layered, non-delaminated MXene particles by electrochemical characterization of two common MXenes (Ti3 C2 T x and V2 CT x ) with various electrolytes and at elevated temperatures, complemented by DFT calculations. Our experimental results show poor reversible capacities (<5 mA h g −1 ) both at room temperature and at 60 °C, indicating that no intercalation of Mg ions occurs during cycling. DFT simulations show that Ti3 C2 T2 with fluorine and hydroxyl termination groups has a negative average voltage for Mg 2+ and reveal high migration barriers for oxygen termination groups, supporting the experimental results. The DFT calculations also reveal that upon magnesiation in multi-layered V2 CF2 and V2 C(OH)2, MgF2 or MgH2 is formed rather than the electrochemical intercalation of Mg 2+ . However, multi-layered V2 CO2 is found to have both a relatively high theoretical average voltage (∼1.5 V) and a comparatively low migration barrier of 480 meV, allowing for Mg 2+ intercalation and RMBs with energy densities comparable to Li-ion batteries. The findings emphasize the need to fully control the MXene termination groups. The possible reasons for the unsatisfactory and deviant electrochemical performance reported in this work and in the literature are critically reviewed to assess the feasibility of MXene cathodes for energy-dense RMBs.